Designing Business System Model Using System Modeling Approach to the Small and Medium Enterprises (SME) of Furniture in Indonesia - Irwan Sukendar; Wiwiek Fatmawati; Imam Much Ibnu Subroto; Rizki Arigama (IAES Indonesia Section, 2016)
This paper studies the design of business system model with System Modeling Approach on small and medium enterprises (SMEs) of furniture. Methods used consists of five phases: phase of identification of business processes actual on SMEs of Furniture, phase of identification of deficiencies and improvement of business processes, phase of design algorithm and flowchart business processes, phase of analysis of the elements of the system, and phase of the design of data flow diagram (DFD), The results of the analysis of the elements of the system are: Products and quantities ordered product consumers and DP paid by consumers identified as elements of system inputs 1,2 and 3. The result of the calculation, payment slips and mail order (SO) are identified as elements of system output 1, 2 and 3. Acceptance of orders, stocks checking of raw materials at the warehouse, calculating raw material requirements, adequacy of raw materials, the price of the contract, and the due date, as well as the submission of the results of calculations to consumers were identified as elements of system components 1, 2, 3, and 4. Admin taking orders, Admin check stocks of raw materials at the warehouse, Admin making calculation, and Admin convey the results of calculations to consumers were identified as an element of interaction system 1, 2, 3, and 4. Consumers were identified as element of environmental systems. Moreover, the boundary between SMEs and consumers were identified as elements of the system boundary.